INHERITANCE INSIGHTS: UNVEILING FARAID AWARENESS IN KUALA LIPIS, PAHANG - Wan Jusoh, Wan Noor Hazlina; Salehen, Abdul Hannan Mohd (Jurnal 'Ulwan, 2024)
The distribution of property among deceased heirs can be resolved by the implementation of Faraid, which is a recognised method. The role of faraid in the management of estate distribution is significant; yet, if not administered and comprehended correctly, this method of wealth transfer might give rise to certain issues. According to estimates in Malaysia, a significant sum of RM42 billion in Muslim inheritance has remained undistributed to its legitimate heirs due to various challenges. Several elements have been recognised as contributing to the issue, including the inefficiency of the administrative system, the attitudes of the community, and the attitudes of the heir. Moreover, the limited dissemination of information regarding the legal principles of faraid contributes significantly to the prevailing lack of awareness of the application of scientific methodologies in the process of Islamic inheritance division. The objective of this study is to examine the extent of awareness on faraid within the Muslim community. This research utilised a quantitative approach by administering an online questionnaire to the Muslim community in Kuala Lipis, Pahang. Convenience sampling was employed to gather data, resulting in a sample size of 102 participants. The results indicate that a significant proportion of the participants has a considerable degree of awareness on faraid. However, this conclusion is limited in its ability to generalise to the broader community due to the small sample size relative to the population size. Hence, it is very advisable to increase the sample size for future research endeavours.